2023
DOI: 10.1071/an22451
|View full text |Cite
|
Sign up to set email alerts
|

Skim-Nanopore sequencing for routine genomic evaluation and bacterial pathogen detection in cattle

Abstract: Context Genotyping-by-sequencing, the use of sequence reads to genotype single-nucleotide polymorphisms (SNPs), has seen an increase in popularity as a tool for genomic prediction. Oxford Nanopore Technologies (Nanopore) sequencing is an emerging technology that produces long sequence reads in real-time. Recent studies have established the ability for low-coverage Nanopore sequence data to be used for genomic prediction. However, the value proposition of Nanopore sequencing for individuals could be improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The accuracies achievable with QUILT at 0.1 × sequencing coverage suggest multiplexing of up to 40 human genome size samples on a single MinION (or up to 200 on a PromethION) flow cell could be possible. This would bring the reagent cost of this method down to below USD $40 per sample, while providing results in under 24 h [ 47 ]. With further optimisation of SNP panel design and the incorporation of new ONT technologies, the level of multiplexing possible will increase further still, making near real-time genomic prediction practically and economically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracies achievable with QUILT at 0.1 × sequencing coverage suggest multiplexing of up to 40 human genome size samples on a single MinION (or up to 200 on a PromethION) flow cell could be possible. This would bring the reagent cost of this method down to below USD $40 per sample, while providing results in under 24 h [ 47 ]. With further optimisation of SNP panel design and the incorporation of new ONT technologies, the level of multiplexing possible will increase further still, making near real-time genomic prediction practically and economically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Underpinning the application of vaccines in this manner could be the emergence of next-generation sequencing technologies to rapidly inform the most appropriate pathogen repertoire for the feedlot of interest [ 166 , 167 , 168 ]. When combined with other types of genetic testing, pathogen detection via these emerging technologies has the potential to inform vaccine coverage in a highly cost-effective manner [ 169 ].…”
Section: Development Of Mrna Vaccines For Important Livestock Diseasesmentioning
confidence: 99%
“…Most of the research reported the applications of the nanopore sequencing method on various pathogens of human beings. However, this method was also effective in the pathogenic diagnostics of plants, animals, and environmental samples [26,[45][46][47]. For example, different phytopathogenic and endophytic fungi such as Cladosporium, Didymosphaeria, Paraconiothyrium, Penicillium, Phoma, and Verticillium species were detected in the olive tree using ONT sequencing for three DNA loci of ITS, betatubulin, and 28S LSU regions [48].…”
Section: Nanopore Sequencing Technology In Pathogenic Diagnosticsmentioning
confidence: 99%